2020
DOI: 10.3390/su122410616
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Adoption and Financial Sustainability: Learned Lessons from Developing Countries

Abstract: Social Media (SM) is considered one of the most discussed topics in today’s business environment, mostly because of the recent developments and improvements in computer and ICT (Information and Communications Technology) technologies. However, very little is known about Social Media’s (SM) role in creating Small and Medium-sized Enterprises’ (SMEs’) financial sustainability. Drawing upon the Technology Organisational and Environmental (TOE) framework, the authors constructed a comprehensive model that examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 102 publications
2
35
0
1
Order By: Relevance
“…The publication established that constant connectivity through social media entices customers to regularly purchase the firm's products or services. Given this, SMEs constantly achieve an increase in sales volume, which subsequently leads to an increase in the bottom line (Rahman et al, 2020;Botchway et al, 2020). Wardati and Er, (2019) also researched the impact of social media usage on the sales process in Small and Medium enterprises and concluded that social media as an advertising tool by SMEs enabled them to improve the sales volume and reduce the selling processes.…”
Section: Financial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The publication established that constant connectivity through social media entices customers to regularly purchase the firm's products or services. Given this, SMEs constantly achieve an increase in sales volume, which subsequently leads to an increase in the bottom line (Rahman et al, 2020;Botchway et al, 2020). Wardati and Er, (2019) also researched the impact of social media usage on the sales process in Small and Medium enterprises and concluded that social media as an advertising tool by SMEs enabled them to improve the sales volume and reduce the selling processes.…”
Section: Financial Performancementioning
confidence: 99%
“…As such, although social media was initially rejected by Small Medium Enterprises for several reasons, it was later adopted based on its business opportunities and strategies (Kallier, 2017). Social media as a strategic advertising tool has facilitated SME's sustainability, brand awareness, acquisition of information, purchase behavior, postpurchase communication, and evaluation of consumer decision-making processes (Rahman et al, 2020). Therefore, small and medium enterprises are significantly innovating and intensifying their business strategies.…”
Section: Financial Performancementioning
confidence: 99%
“…The company reputation is an essential driver to increase its marketing value (Jenck et al, 2004). A positive company brand takes years to build but can be ruined in a matter of minutes with current media coverage and social media campaigning (Ur Rahman, et al, 2020;Raghubansie, et al, 2013;Weybrecht, 2014;and El-Gohary, 2010). Investor relation and the marketing departments within companies perceive green practices as a communication channel through which they can display environmental initiatives (Ross, 2015;and Falsen and Johansson, 2015).…”
Section: Enhanced Corporate Imagementioning
confidence: 99%
“…In addition, Milford et al (2014) illustrated that added difficulties are attached, particularly with financing clean energy projects. However, financial sustainability and green investments remain important globally (Ur Rahman et al, 2020). Getting past the traditional financing system's constraints means that more tailored and innovative finance mechanisms need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…One may see that is positioned in a more holistic way that integrates with other leadership aspects. When we look into leadership from a psychological and sustainable perspective, the aforementioned holistic view of leadership (HCSL) becomes highly significant for the development and for proper functioning of the human resource at organisations (Di Fabio and Peiró, 2018; Ur Rahman et al , 2020). A prior study by Di Fabio and Peiro (2018) further promoted the idea of the integration of the aforementioned sustainability leadership with the other leadership behaviours, like ethical leadership, mindful leadership and servant leadership.…”
Section: Conceptual Framework and Hypothesismentioning
confidence: 99%